ALI Analysis Guarantee Law On State Civil Apparatus Decree As A Basis Of Guarantee For Banking Credit Application: Analysis Guarantee Law On State Civil Apparatus Decree As A Basis Of Guarantee For Banking Credit Application - Mohamad Ali (CV Rewang Rencang, 2024)
That the current economic conditions and development in Indonesia cannot be separated from the role and function of existing banking, because banking is a